The Types of Respect About the President Joko Widodo’s Government by Netizen on Tiktok Comment - Mahmud, Murni; Burhamzah, Muftihaturrahmah; Utami, Andini Putri (Pascasarjana Universitas Negeri Makassar, 2025)
This study investigates how netizens express respect toward President Joko Widodo’s government through comments on TikTok, one of the most influential digital platforms used by Indonesian youth. Respect, as a moral and social construct, encompasses both recognition of an individual’s status and appraisal of their actions. Using a qualitative descriptive approach, thirty TikTok comments were purposively selected from five highly viewed accounts discussing Jokowi’s leadership. The data were analyzed through discourse analysis to identify linguistic expressions of recognition respect and appraisal respect in the comments. The findings indicate that netizens display appraisal respect by praising concrete policy outcomes such as pandemic assistance (free electricity credit, food subsidies, and monthly allowances), social welfare programs (BPJS and KIP), and infrastructure development (including toll roads and renewable energy projects). Recognition respect emerges through acknowledgment of Jokowi’s leadership qualities, including sincerity, humility, patience, and simplicity, as well as his symbolic status as a national figure. Emotional expressions, such as sadness toward his retirement and admiration for his legacy, further demonstrate the affective dimension of political respect in digital communities. The results suggest that respect in online political discourse is multidimensional, combining evaluative appreciation of governmental achievements with recognition of leadership identity. This research contributes to understanding how youth-dominated digital spaces construct political respect and provide insight into contemporary perceptions of governance in Indonesia.